The Relationship Between Physical Activity and Hypertension Prevention in Adolescents - Agustin, Ira; Susanti, Nofi; Assyfa, Vazira Nurul; Lubis, Naila Salsabila (PROMOTOR, 2025)
Hypertension or high blood pressure is a serious health problem and is common among teenagers. Hypertension is not only a major cause of cardiovascular disease, but also contributes significantly to the global health burden. According to data from the 2023 Indonesian Health Survey (SKI), the prevalence of hypertension in Indonesia has reached an alarming figure. This research method uses quantitative methods by collecting data through questionnaires. This questionnaire is designed to measure the independent variable, namely physical activity, and the dependent variable, namely blood pressure. Based on the results of the questionnaire, physical activity and blood pressure data were obtained from 32 respondents. Data was collected through questionnaires distributed to 32 teenagers aged 18 to 22 years. Based on Table 2, the correlation between frequency of physical activity (∑x1) and blood pressure (∑y) is 0.413* with p 0.019. This shows that there is a significant positive relationship between how often adolescents engage in physical activity and their blood pressure. These results emphasize the importance of promoting physical activity among adolescents as a hypertension prevention strategy. Physical activity is not only beneficial for cardiovascular health but also plays an important role in maintaining overall health.